Implication Of Lamaholot Local Wisdom On Learning Indonesian Language and Literature - Pande, Rikardus (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2025)
This study aims to describe the implications of Lamaholot local wisdom on learning Indonesian language and literature. The research method uses a qualitative method. The implications of Lamaholot local wisdom in learning Indonesian language and literature provide benefits through creativity and noble values of local wisdom with the following conclusions, (1) making Lamaholot local wisdom as teaching materials taken from the cultural wealth in the Lamaholot area, (2) teaching Lamaholot local wisdom using certain and special methods through direct practice to direct students, students can understand, find, transcribe culture, analyze, interpret, explain and implement in everyday life. (3) through Lamaholot local wisdom learning activities, teachers or educators can create learning strategies that further encourage student motivation to understand, interpret and have cultural wisdom, and (4) through Lamaholot local wisdom learning can provide benefits for students to uphold the values and characters of cooperation, honesty, responsibility, courage, religiosity, morals, social as the foundation of life.